2022
DOI: 10.3389/fonc.2022.863094
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an 8-Gene Signature to Improve Survival Prediction of Colorectal Cancer

Abstract: BackgroundMost prognostic signatures for colorectal cancer (CRC) are developed to predict overall survival (OS). Gene signatures predicting recurrence-free survival (RFS) are rarely reported, and postoperative recurrence results in a poor outcome. Thus, we aim to construct a robust, individualized gene signature that can predict both OS and RFS of CRC patients.MethodsPrognostic genes that were significantly associated with both OS and RFS in GSE39582 and TCGA cohorts were screened via univariate Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…For example, Ma J et al identified 5 prognosis-related markers in triple-negative breast cancer and provided potential therapeutic targets through multiomics and bioinformatics (22). Zhou L et al developed an 8-gene signature to predict overall survival in colon cancer patients (23). However, similar research in gliomas was significantly less common than in other tumours, implying that more comprehensive and in-depth studies of gliomas are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ma J et al identified 5 prognosis-related markers in triple-negative breast cancer and provided potential therapeutic targets through multiomics and bioinformatics (22). Zhou L et al developed an 8-gene signature to predict overall survival in colon cancer patients (23). However, similar research in gliomas was significantly less common than in other tumours, implying that more comprehensive and in-depth studies of gliomas are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou L et al. developed an 8-gene signature to predict overall survival in colon cancer patients ( 23 ). However, similar research in gliomas was significantly less common than in other tumours, implying that more comprehensive and in-depth studies of gliomas are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate Cox regression analysis was performed to screen the prognosis-related nAChRs among the smoking population in the HNSCC cohort. To avoid overfitting, least absolute shrinkage and selection operator (LASSO) analysis was performed, and a novel prognostic signature was constructed using the following formula: risk score = nAChR (A) expression * coef (A) + nAChR (B) expression * coef (B) + nAChR (i) expression * coef (i) [ 15 ]. Based on the expression of nAChRs, the risk of each of the patients was scored and they were divided into low- and high-risk groups according to the median value.…”
Section: Methodsmentioning
confidence: 99%
“…Univariate Cox regression analysis was used to evaluate the association between genes and NPC prognosis. DEGs that were significantly associated with NPC (P<0.05) were considered as candidate genes ( 26 ). Subsequently, the glmnet package in R was used to filter and remove genes that might result in overfitting the model by the Lasso algorithm.…”
Section: Methodsmentioning
confidence: 99%